Meta-Analysis: Smoking and Proverty as Risk Factors of Tuberculosis Multidrug Resistance - Bibit Irawan; Sumardiyono Sumardiyono; Bhisma Murti (Journal of Health Promotion and Behavior, 2022)
Background: The financing burden for tuberculosis treatment is increasing along with the increasing number of cases of Multidrug Resistant Tuberculosis (MDR-TB). The main problems that arise in MDR-TB patients are difficult and expensive treatment, high mortality rates and the potential to transmit resistant bacilli to others. The purpose of the study was to estimate the magnitude of the influence of smoking behavior and poverty on the incidence of MDR-TB.Subjects and Method: This was a meta-analysis with PICO, population: active patients on TB treatment. Intervention: Smoking behavior and poverty. Comparison: not smoking and not poor. Result: MDR TB. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are “poverty” OR “smoking” AND “multidrug resistant tuberculosis”. Articles included are full-text English from 2012 to 2022. Articles were selected using a PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application. Results: A total of 12 articles came from the continents of Asia (China India, Indonesia), Africa (Sudan, Ethiopia, Tanzania), North America (Georgia), and South America (Peru). The results of this meta-analysis showed that smoking increased the risk of MDR TB 1.94 times compared to those who did not smoke (aOR = 1.94; 95% CI = 1.64 to 2.30; p = 0.005), and poverty increased the risk of MDR TB 1.85 times compared to those who did not. not in poverty (aOR= 1.85; 95% CI= 1.35 to 2.53; p= 0.004), and both results were statistically significant.Conclusion: Smoking behavior and poverty increase the risk of MDR TB.Keywords: smoking behavior, poverty, MDR TB.Correspondence:Bibit Irawan. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: irawanbibit@gmail.com. Mobile: +6293111570225.Journal of Health Promotion and Behavior (2022), 07(04): 284-298DOI: https://doi.org/10.26911/thejhpb.2022.07.04.02